수술 후 발생한 Corynebacterium Striatum 복강 내 감염 - 최현석; Hyun Seok Choi; 김주승; Ju Seung Kim; 정을식; Eul Sik Jung; 김애진; Ae Jin Kim; 정한; Han Jung; 박윤수; Yoon Soo Park; et al. (The Korean journal of medicine, 2012)
Corynebacterium striatum is an aerobic, Gram-positive bacillus that is part of the resident flora of skin and mucosal membranes. C. striatum is usually considered a non-pathogenic contaminant, although infective endocarditis and respiratory infection, and less frequently arthritis and meningitis, due to C. striatum have been reported. C. striatum has been particularly associated with catheter-related infections and infections following conditions that resulted in disruption of the skin barrier in both immunocompromised and immunocompetent hosts. We describe a case of post-operative intra-abdominal infection caused by the rare pathogen, C. striatum. (Korean J Med 2012;82:516-519)